Dynamic postural control in 2 to 6 years old children - Feitosa, Erlane Aguiar; Rinaldi, Natália Madalena; Gobbi, Lilian Teresa Bucken (Brazilian journal of physical education and sport, 2008)
The development of postural control has been studied under different experimental paradigms. Most of them used tasks that require the maintenance of quiet stance. The aim of this study was to investigate the developmental changes in postural control in a dynamic balance task. The experimental task was to stand on a force plate for 30 seconds keeping the quiet stance posture during the first 15 seconds, reaching and grasping a toy on a table (left medial-lateral movement) and bringing it close to the chest during the last 15 seconds. Mean sway amplitude (MSA) in the medial-lateral direction was established as the dependent variable for each task phase. Main effects of age group were found in phase 3 (bringing the toy to the chest).MSA significantly increased between the first and the last 15 seconds of the task. Results allowed us to conclude that developmental changes in postural control occurred in dynamic balance tasks.